WAYS TO DETERMINE AND HOW TO APPLY POLITENESS VALUES IN ENGLISH CLASSROOM - Nurul Fitri (Proceedings of ISELT FBS Universitas Negeri Padang, 2018)
Every culture has its own ways in applying its norms and politeness values.  Some things that are considered polite in one culture could be considered impolite in another. This greatly affects the utilization of politeness value that is used by students in English textbooks that they use compared to their own culture that would creates some questions about politeness like which politeness value that they are supposed to use. Besides, politeness values in Eastern country like Indonesia are very prominent. The culture in Indonesia usually uses negative politeness values in conversations. This paper explains about the importance of norms and politeness values in interaction within English class. The purpose of this paper is to describe the English learning that is not only taken from textbooks but also inserts the politeness values of that very culture in order to enable the students in comparing and determining the forms and differences between those two politeness values. This paper is expected to give valuable contribution to English teachers in junior and senior high school about how to see the difference between politeness values of textbooks and their own culture and how to apply the politeness values shown on the English textbooks.